Analysis of Population Composition: Dynamics of Population Composition and Development of Pekanbaru City - Amelia, Hutri Rizki; Saputra, Hendra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Pekanbaru City, the capital of Riau Province, faces the region's highest unemployment rate, posing a challenge to its development. Targeted policies are crucial, aligning with the unique characteristics of Pekanbaru City's population. Achieving development goals requires a nuanced understanding of population composition. This quantitative descriptive study investigates population data from 2016 to 2020 for Pekanbaru City, unveiling annual fluctuations in age-based composition and a consistently low dependency ratio. The findings indicate: (1) The age-based population composition underwent yearly fluctuations from 2016 to 2020; (2) The dependency ratio in Pekanbaru City between 2016 and 2020 exhibited dynamic trends, consistently remaining in the low category. This suggests that a significant proportion of Pekanbaru City's population falls within the productive age range. To optimize the potential of this demographic, recommended initiatives involve investing in training and skills development, along with facilitating enhanced access to financing for Micro, Small, and Medium Enterprises (MSMEs). These strategic measures aim to leverage the strength of Pekanbaru City's productive age population, fostering economic growth and development.